MERGER ACQUISITION IN THE INDONESIAN CONTEXT - Indra; Mardalena; Siti Bakdiah; Raja Rafiza; Fakhrul Razak; Indrayani; Muammar Khaddafi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Merger and acquisition activities have been carried out not only in developed countries but also in Southeast Asia. In ASEAN countries investment activities carried out between countries reached US$ 4.4 billion in 2009, of which most were carried out in Singapore (46%), Indonesia (31%) and Thailand (13%) (KPPU, 2010). These three countries have various investment regulations, especially those related to mergers and acquisitions. This is important for maintaining competitive and efficient market activities. For regulations related to mergers and acquisitions, only 5 (five) ASEAN countries have competition laws, namely Indonesia, Singapore, Thailand, Vietnam and Laos. Merger and acquisition rules owned by each country vary from various aspects, be it the scope, nature of notification, financing, and related sanctions.